The Shiny Seventh The 7th (Service) Battalion Bedfordshire Regiment at War, 1915-1918. - Deacon, M. G. (Publications Bedfordshire Hist Rec Soc Series., 2004)
The Shiny Seventh was an ordinary Kitchener battalion, a body of men raised for the duration of the war, forming part of an ordinary county regiment.